Effect of Heat, Time and UV Light on Different Brands of Fluconazole by UV Spectrophotometeric Method - Naveed, Safila; Waheed, Nimra; Ashraf, Zehra; Nazeer, Safeena; Qamar, Fatima; Dilshad, Huma; Zafar, Farya; Ali, Huma (Asian Journal of Chemistry, 2016)
Fluconazole i.e., 2,4-difluoro-a,a¢-bis(1H-1,2,4-triazol-1-ylmethyl)benzyl alcohol belongs to the class of drug antifungal (subclass of synthetic triazole). The purpose of this research is to study the effect of acid and base by using UV spectrophotometry, on different brands of fluconazole under ICH guideline Q1A (R2). According to USP, fluconazole contains calcium not less than 98 % and not more than 102 % of C13H12N6OF2, calculated on the anhydrous basis. The result of the study concluded that chosen brands of fluconazole i.e. hiflucan (A), arsozole (B) and zolanex (C), were used for evaluating the effect of UV light, time and heat. When the three chosen brands of fluconazole; hiflucan (A), arsozole (B) and zolanex (C) were subjected to heat for 0, 30 and 60 min, no degradation was observed in brand A at 30 and 60 min, slight degradation was observed in brand B at 30, 60 min and significant degradation was observed in brand C at 30 and 60 min. When different brands of fluconazole were subjected to UV light, slight degradation were observed in brand A (86.39 %) and significant degradation were observed in B and C (73.61 %) and (69.15 %) respectively. Similarly when 3 different brands of fluconazole were left for a week, no degradation was observed in brand A, slight degradation was observed in brand B and C respectively.